Reprogramming neuroblastoma by diet-enhanced polyamine depletion - Sarah Cherkaoui; Christina S. Turn; Yuan Yuan; Wenyun Lu; Lifeng Yang; Matthew J. McBride; Caroline Eigenmann; George E. Allen; Olesya O. Panasenko; Lu Zhang; Annette Vu; Kangning Liu; et al. (Nature, 2025)
Abstract Neuroblastoma is a highly lethal childhood tumour derived from differentiation-arrested neural crest cells1,2. Like all cancers, its growth is fuelled by metabolites obtained from either circulation or local biosynthesis3,4. Neuroblastomas depend on local polyamine biosynthesis, and the inhibitor difluoromethylornithine has shown clinical activity5. Here we show that such inhibition can be augmented by dietary restriction of upstream amino acid substrates, leading to disruption of oncogenic protein translation, tumour differentiation and profound survival gains in the Th-MYCN mouse model. Specifically, an arginine- and proline-free diet decreases the amount of the polyamine precursor ornithine and enhances tumour polyamine depletion by difluoromethylornithine. This polyamine depletion causes ribosome stalling, unexpectedly specifically at codons with adenosine in the third position. Such codons are selectively enriched in cell cycle genes and low in neuronal differentiation genes. Thus, impaired translation of these codons, induced by combined dietary and pharmacological intervention, favours a pro-differentiation proteome. These results suggest that the genes of specific cellular programmes have evolved hallmark codon usage preferences that enable coherent translational rewiring in response to metabolic stresses, and that this process can be targeted to activate differentiation of paediatric cancers.